2017
DOI: 10.1002/glia.23239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of X‐irradiation on microglia

Abstract: Irradiation is widely used to treat brain tumors, and also to create bone marrow (BM) chimeras.BM chimeras are widely used to dissect functions and origin of microglia and blood-derived mononuclear cells under homeostatic or pathological conditions. This is facilitated by the fact that microglia survive irradiation and are thus regarded radio-resistant. In this study, we tested whether microglia are indeed radio-resistant and looked for potential mechanisms that might explain this phenomenon. We analyzed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
(122 reference statements)
0
13
0
Order By: Relevance
“…These data indicate that monocytes are capable of outcompeting endogenous CSF1Ri-resistant microglia under these conditions. Previous data has shown that microglia survive cranial irradiation, however do exhibit increased activation and decreased cell number [ 81 ], and that irradiation induces loss of proliferating cells, including progenitor/stem and microglial cells [ 60 ]. Thus, in order to induce complete monocyte engraftment, it appears that the brain must possess an empty microglial niche or microglial cells that lack the ability to proliferate/self-renew.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that monocytes are capable of outcompeting endogenous CSF1Ri-resistant microglia under these conditions. Previous data has shown that microglia survive cranial irradiation, however do exhibit increased activation and decreased cell number [ 81 ], and that irradiation induces loss of proliferating cells, including progenitor/stem and microglial cells [ 60 ]. Thus, in order to induce complete monocyte engraftment, it appears that the brain must possess an empty microglial niche or microglial cells that lack the ability to proliferate/self-renew.…”
Section: Discussionmentioning
confidence: 99%
“…We are beginning to recognize that activated microglia are also quite plastic cells that may differentiate into a plethora of subsets and perform various functions in response to different stimuli and environmental changes such as obesity, diet, alcohol, and even the host microbiota (Chunchai, Chattipakorn, & Chattipakorn, ; Erny et al, ; Hanamsagar & Bilbo, ; Henriques et al, ; Johnson, ; Mathys et al, ; Menzel et al, ). In support of this, it has recently been reported that microglia can even respond to microbial challenges during embryogenesis, and that the absent status of a microbiome has a quite different impact on both age‐ and sex‐specific microglial gene expression (Thion et al, ).…”
Section: Subsets Of Microglia: More Than Pro‐inflammatory and Immunormentioning
confidence: 99%
“…However, a major caveat of this approach is that robust donor HSC engraftment requires the elimination of the host blood system by high doses of irradiation, upwards of 10 Gy (or 1,000 Rads). This can have long‐term effects on the brain environment, by activating microglia, modifying pathology and disrupting the blood brain barrier (BBB; Menzel et al, ). Moreover, a follow‐up study from the same group and others showed that shielding the head during irradiation to reduce BBB disruption, or use of parabiosis resulted in little to no contribution of bone marrow‐derived cells to the PAM population, despite robust bone marrow engraftment and donor peripheral immune cell reconstitution (Lampron, Lessard, & Rivest, ; Mildner et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%